3D digital outcrop model-based analysis of fracture network along the seismogenic Mt. Vettore Fault System (Central Italy): the importance of inherited fractures. (August 2022) - Panara, Yuri; Menegoni, Niccolò; Carboni, Filippo; Inama, Riccardo
Abstract: The Mt. Vettore area is located in the Central Apennines (Italy), a region characterized by intense seismic activity that has recorded multiple moderate-to-high magnitude seismic sequences. The seismic activity is due to the presence of normal fault systems, among which is the Mt. Vettore Fault System (VFS), which was last activated during the 2016-17 Central Italy seismic sequence.. Moreover, the region has experienced three major tectonic phases over geological history, thus it is important to unravel their contribution to the current fracture network. Based on the integration of field observation with Unmanned Aerial Vehicle - Digital Photogrammetry data, we aim to analyze the fracture network on eight different outcrops located at different structural positions with respect to VFZ. Results show that the Late Miocene−Early Pliocene compressional phase deeply affected the present-day fracture pattern, which is especially related to the evolution of the Mt. Sibillini regional thrust and its related anticline. The present-day Quaternary extensional phase, and the associated normal faults, mostly reactivate some of the pre-existing fracture sets. Highlights: Definition of the main fracture sets in the Jurassic Calcare Massiccio formation in the Mt. Vettore Area. Definition of the fracture intensity variation in different structural position along the study area. Definition of the cross cutting relation between the main fracture sets.